Influence of planting time interval with dose of local organic liquid fertilizer (Lof-nachi) on growth and production of cowpea (Vigna unguiculata L.) in Ermera municipality - Pereira, Marcos; da Costa Belo, Cecilio Alves; Pereira, Inácio Savio; Ninas Nabais, Claudino (Politeknik Siber Cerdika Internasional, 2026)
This study aimed to determine the optimal planting time interval and dose of local organic liquid fertilizer (Lof-nachi) for the growth and yield of cowpea (Vigna unguiculata L.) plants. The experiment was conducted over six months, from May to October 2024 in Fatuqueru Village, Railaco Administrative Post, Ermera municipality, located at an altitude of 880 m above sea level with an annual rainfall of approximately 2,000 mm. A split-plot experimental design (3 × 3 factorial) was employed, with two factors: planting time interval and dose of local liquid fertilizer. Results showed that productivity parameters were significantly influenced by the interaction between planting time interval and fertilizer dosage. Three yield parameters from the combined treatments showed significant differences. The number of pods and fruit length were significantly different (p < 0.01), while the overall yield parameter was highly significant (p < 0.001). The highest yield was obtained from the two-week planting interval combined with a fertilizer dose of 1,500 L/ha (I2A2), producing 3.51 t/ha. In contrast, the lowest yield was recorded in the control treatment (I0A0), with 1.47 t/ha. These findings highlight the importance of optimizing both planting schedules and organic fertilizer application to enhance cowpea productivity under local agro-ecological conditions.